Sequential Organ Failure Assessment Score As a Predictor of Outcome in Sepsis in Pediatric Intensive Care Unit - Lalitha, A.V.; Satish, J.K.; Reddy, Mounika; Ghosh, Santu; George, Jiny; Pujari, Chandrakanth (Journal of Pediatric Intensive Care, 2020)
Sequential organ failure assessment (SOFA) score is used as a predictor of outcome of sepsis in the pediatric intensive care unit. The aim of the study is to determine the application of SOFA scores as a predictor of outcome in children admitted to the pediatric intensive care unit with a diagnosis of sepsis. The design involved is prospective observational study. The study took place at the multidisciplinary pediatric intensive care unit (PICU), tertiary care hospital, South India. The patients included are children, aged 1 month to 18 years admitted with a diagnosis of sepsis (suspected/proven) to a single center PICU in India from November 2017 to November 2019. Data collected included the demographic, clinical, laboratory, and outcome-related variables. Severity of illness scores was calculated to include SOFA score day 1 (SF1) and day 3 (SF3) using a pediatric version (pediatric SOFA score or pSOFA) with age-adjusted cutoff variables for organ dysfunction, pediatric risk of mortality III (PRISM III; within 24 hours of admission), and pediatric logistic organ dysfunction-2 or PELOD-2 (days 1, 3, and 5). A total of 240 patients were admitted to the PICU with septic shock during the study period. The overall mortality rate was 42 of 240 patients (17.5%). The majority (59%) required mechanical ventilation, while only 19% required renal replacement therapy. The PRISM III, PELOD-2, and pSOFA scores correlated well with mortality. All three severity of illness scores were higher among nonsurvivors as compared with survivors (p < 0.001). pSOFA scores on both day 1 (area under the curve or AUC 0.84) and day 3 (AUC 0.87) demonstrated significantly higher discriminative power for in-hospital mortality as compared with PRISM III (AUC, 0.7), and PELOD-2 (day 1, [AUC, 0.73]), and PELOD-2 (day 3, [AUC, 0.81]). Utilizing a cutoff SOFA score of >8, the relative risk of prolonged duration of mechanical ventilation, requirement for vasoactive infusions (vasoactive infusion score), and PICU length of stay were all significantly increased (p < 0.05), on both days 1 and 3. On multiple logistic regression, adjusted odds ratio of mortality was elevated at 8.65 (95% CI: 3.48–21.52) on day 1 and 16.77 (95% confidence interval or CI: 4.7–59.89) on day 3 (p < 0.001) utilizing the same SOFA score cutoff of 8. A positive association was found between the delta SOFA ([Δ] SOFA) from day 1 to day 3 (SF1–SF3) and in-hospital mortality (chi-square for linear trend, p < 0.001). Subjects with a ΔSOFA of ≥2 points had an exponential mortality rate to 50%. Similar association was—observed between ΔSOFA of ≥2 and—longer duration of inotropic support (p = 0.0006) with correlation co-efficient 0.2 (95% CI: 0.15–0.35; p = 0.01). Among children admitted to the PICU with septic shock, SOFA scores on both days 1 and 3, have a greater discriminative power for predicting in-hospital mortality than either PRISM III score (within 24 hours of admission) or PELOD-2 score (days 1 and 3). An increase in ΔSOFA of >2 adds additional prognostic accuracy in determining not only mortality risk but also duration of inotropic support as well.
Keywords: SOFA score; PELOD-2; PRISM III; outcome prediction; septic shock